Box-Behnken Design employed stability demonstrating RP-HPLC method development of sorafenib tosylate for rapid and sensitive quantification (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Sorafenib tosylate (SFN) is a tyrosine kinase inhibitor used clinically to treat liver, kidney, and thyroid carcinoma. This research aims to accurately quantify SFN using a quality-by-design (QbD) approach with RP-HPLC. Chromatographic settings were optimized using a Box-Behnken design, measuring responses such as retention time, tailing factor, theoretical plate, and peak area. At the same time, independent variables were flow rate, mobile phase composition, and wavelength. A C18 column (4.6 × 250 mm, 5 µm) served as the stationary phase, with a mobile phase of methanol and 0.1% o-phosphoric acid in a 41:59 v/v ratio. SFN detection occurred at 267 nm in isocratic mode at a flow rate of 1.1 mL min−1. Method validation followed International Council for Harmonization guidelines, yielding a coefficient of determination (R2) of 0.9998, indicating linearity in the 5-25 µg mL−1 range. Results showed detection (LOD) and quantification (LOQ) limits of 0.04 and 0.12 µg mL−1, respectively. Additionally, the method demonstrated precision, accuracy, and robustness consistent with ICH criteria. Overall, this simple, accurate, rapid, and robust RP-HPLC method is suitable for routine SFN analysis in various formulations.